Hacker and the Treat for National Security: Challenges in Law Enforcement - Rais, Muhammad Amin; Songkarn, Phichit (Faculty of Law Universitas Negeri Semarang, 2022)
Globalization has become the driving force behind the birth of the era of information technology development. The development of this technology is very fast and has spread to all corners of the world. The development of information technology is not only felt by developed countries but developing countries also feel the development of information technology, so that information technology gets an important position for the progress of society in this modern era. The need for computer network technology is increasing. Apart from being a medium for providing information, through the internet, commercial community activities are also the largest and growing rapidly and penetrate various national borders. Even through this network market activities in the world can be known for 24 hours. Through the world of the internet or also called cyber space, anything can be done. The positive side of this virtual world of course adds to the trend of world technology development with all forms of human creativity. However, the negative impact cannot be avoided. When pornography is rife on the internet, people can't do much. Along with the development of internet technology, causing the emergence of a crime called cyber crime or crime through the internet network or cyberspace. The emergence of several cases of cyber crime in Indonesia, such as credit card theft, hacking of several sites, tapping other people's data transmissions, such as e-mail and manipulating data by preparing unwanted commands into computer programmers. So that in computer crimes it is possible to have formal offenses and material offenses. Formal offense is the act of someone entering someone else's computer without permission, while material offense is an act that causes harm to other people. The existence of cyber crime has become a threat to stability, so it is difficult for the government to balance the techniques of crime committed with computer technology, especially in the internet network.